Intrahospital transport of mechanically ventilated intensive care patients using new equipment attached to a transfer board. Issue 3 (28th April 2015) - Matsumura, Yosuke; Nakada, Taka‐aki; Hayashi, Yosuke; Oshima, Taku; Oda, Shigeto
Abstract : Aim: Multiple lines and tubes often complicate bed transfer in critically ill patients. To solve this problem, the authors developed medical equipment attached to a transfer board ("transfer board tree") that integrates the patient, transfer board, and medical equipment. The objective of this study was to evaluate the efficiency and safety of the transfer board tree. Methods: Forty mechanically ventilated patients (20 transfer board tree, 20 conventional) in the intensive care unit who were transported for computed tomography were enrolled. Transfer times and adverse events were recorded. Results: Transfer board tree patients had significantly shorter transfer times. There were two adverse events only in the conventional group. Conclusions: The transfer board tree enables rapid intrahospital transport of intensive care patients with sufficient monitoring.